Effect of Different Grazing Management Practices on Soil Health in Lasiurus sindicus Grasslands of Arid Western Plain - Panwar, Nav Raten; Roy, Sharmila; Kumar, Mahesh; Pandey, C. B. (Annals of Arid Zone, 2022)
Maintenance of optimal levels of fodder production from grasslands and rangelands require higher importance as in the arid zone, forage species grow under hostile climatic conditions and also bear high grazing pressure. Therefore, a study was undertaken to assess the effect of different grazing management practices in Lasiurus sindicus grasslands on soil chemical and biological properties and carbon management. Silviculture systems, managed pastures and natural grassland with control grazing had significantly higher values for SOC, CMI, MBC and DHA in comparison to the reference soil (undisturbed soil). The grazing management in Lasiurus sindicus based grassland is highly favourable to soil carbon management and soil health improvement. Silvipasture system and controlled grazing in grasslands had a beneficial role in restoring soil health in arid western Rajasthan.